Penggunaan Alat Bukti Sekunder dalam Menjatuhkan Tuntutan Pidana Berdasarkan Asas Kepastian Hukum - Gusriana, Fahmi; Batubara, Gialdah Tapiansari (Universitas Muhammadiyah Ponorogo, 2025)
The use of circumstantial evidence in criminal cases has raised legal debate. Judges in some cases consider circumstantial evidence because there were no eyewitnesses who saw the criminal event directly. This is contrary to the Criminal Code which limits valid evidence in Indonesian criminal procedure law. The use of circumstantial evidence that is not regulated in the Criminal Code has the potential to cause normative conflicts, legal uncertainty, and violations of human rights. It is necessary to examine the criteria for circumstantial evidence that is permitted in the Indonesian criminal procedure law system and has a legal standing in line with the principle of legal certainty, as well as the legal consequences of using circumstantial evidence in imposing criminal charges based on the principle of legal certainty using normative legal research methods with a statutory approach and case studies. The results show that the criteria for circumstantial evidence that is justified in the Indonesian criminal procedure law system and has a legal standing in line with the principle of legal certainty is when the use of circumstantial evidence is prioritized for proving cases where there are no eyewitnesses who saw it directly, its use must be complementary, cannot stand alone (not used as the sole basis for imposing a criminal sentence), its use must meet the elements of accountability, relevance, authenticity, validity, proportionality, not violating human rights, used as complementary evidence that supports the proof and used as part of the consideration of proof, especially in the form of instructions or letters to strengthen the judge's conviction. The legal consequences of the use of circumstantial evidence in imposing criminal charges based on the principle of legal certainty remain normatively legal. As long as the use of circumstantial evidence is in accordance with its position, its use remains in line with the principle of legal certainty as one of the fundamental principles in the Indonesian legal system.